Significant Amplification of Instantaneous Extreme Precipitation With Convective Self‐Aggregation. (18th November 2021) - Da Silva, Nicolas A.; Muller, Caroline; Shamekh, Sara; Fildier, Benjamin
Abstract: This work explores the effect of convective self‐aggregation on extreme rainfall intensities through an analysis at several stages of the cloud lifecycle. In addition to increases in 3‐hourly extremes consistent with previous studies, we find that instantaneous rainrates increase significantly (+30%). We mainly focus on instantaneous extremes and, using a recent framework, relate their increase to increased precipitation efficiency: the local increase in relative humidity drives larger accretion efficiency and lower re‐evaporation. An in‐depth analysis based on an adapted scaling for precipitation extremes reveals that the dynamic contribution decreases (−25%) while the thermodynamic is slightly enhanced (+5%) with convective self‐aggregation, leading to lower condensation rates. When the atmosphere is more organized into a moist convecting region and a dry convection‐free region, deep convective updrafts are surrounded by a warmer environment which reduces convective instability and thus the dynamic contribution. The moister boundary‐layer explains the positive thermodynamic contribution. The microphysic contribution is increased by +50% with aggregation. The latter is partly due to reduced evaporation of rain falling through a moister near‐cloud environment, but also to the associated larger accretion efficiency. Thus, a potential change in convective organization regimes in a warming climate could lead to an evolution of tropical precipitation extremes significantly different than that expected from thermodynamical considerations. The relevance of self‐aggregation to the real tropics is still debated. Improved fundamental understanding of self‐aggregation, its sensitivity to warming and connection to precipitation extremes, is hence crucial to achieve accurate rainfall projections in a warming climate. Plain Language Summary: Heavy precipitation and floods are frequent in the tropics. The spatial organization of weather systems is often associated with these events. Our study investigates the case of convective self‐aggregation which is a particular type of cloud systems' organization observed in idealized numerical simulations. We find that convective self‐aggregation tends to increase rainfall intensities by 30%–70%. There are several processes involved in the formation of heavy rainfall: vertical motion air, condensation into cloud droplets, growth of these droplets into precipitating drops, collection of other cloud‐droplets through their descent and partial re‐evaporation between cloud base and the ground. We examine the contribution of each of these processes and find that the increase in rain rates with convective self‐aggregation is related to both lower rain re‐evaporation and more efficient cloud droplet collection by rain drops through their descent. It is still unclear how heavy rainfall will evolve in a warming climate. While the relationship between temperature and water vapor suggests that heavy rainfall will increase by 7% per 1K, our result shows that a hypothetic change in the organization of weather systems could potentially lead to more dramatic changes in heavy rainfall in a future warming climate. Key Points: Convective self‐aggregation may increase both accumulated and instantaneous rainfall extremes This increased precipitation is related to reduced rain re‐evaporation and enhanced accretion efficiency with convective self‐aggregation Extreme convective updrafts within self‐aggregated convection are weaker due to warmer environment